Hereditary ovarian cancer risk reduction: a retrospective evaluation of patient perspectives and service provision at a regional hereditary gynaecologic cancer clinic 2006-2016 - Lauren Adolph; Ashley Warias; Jocelyn Stairs; Kelly Collins-McNeil; Lynette Penney; Katharina Kieser (BMC, 2022)
Abstract Background Germline pathogenic variants in BRCA1/2 have been established in hereditary breast and ovarian cancer (HBOC) syndrome and result in significantly elevated lifetime risk of ovarian cancer. Risk reduction interventions are presently the only effective means of improving survival and specialized counselling clinics have been established as an effective means of aiding this population in navigating complex decisions surrounding these interventions. This study sought to evaluate patient perceptions of a specialized counselling clinic for patients with HBOC Syndrome and referral patterns to this clinic. Methods We completed a retrospective review of 200 patients with HBOC in Nova Scotia, Canada seen through Maritime Medical Genetics Services between 2006 and 2016. Data were collected on referral pattern to the Hereditary Gynaecologic Risk Reduction Clinic (HGRRC), demographics, health history, and uptake of risk-reducing interventions. Participants were invited to complete a questionnaire about their experience. Results 156/200(78%) women were referred to HGRCC and 135/156 (85.9%) of those referred attended their appointment. 124/200 (62%) were over age 40 at the time of testing. The mean time from referral to HGRCC appointment was 134.68 days (SD 85.78). 85/135 (63%) underwent risk-reducing bilateral salpingo-oophorectomy following their HGRCC appointment. The questionnaire was completed by 94/188 (50.3%) women. Most participants found information received from genetics clinics (81/94; 91%) and genetic counsellors (87/94; 95%) most helpful in making choices around risk-reduction strategies. 83/94 (88%) participants felt they had sufficient information to make an informed decision. Conclusion The majority of women with HBOC in Nova Scotia during the study period were referred to and counselled through HGRRC. Genetic counselling was found most valuable in risk-reduction decision making, which highlights the importance of a multidisciplinary team. Patients viewed this clinic as an effective care model to support informed choice about risk-reducing intervention.